Air‐Spun PLA Nanofibers Modified with Reductively Sheddable Hydrophilic Surfaces for Vascular Tissue Engineering: Synthesis and Surface Modification. Issue 4 (23rd September 2013) - Ko, Na Re; Sabbatier, Gad; Cunningham, Alexander; Laroche, Gaétan; Oh, Jung Kwon; Lutz, J.‐F.; Sumerlin, B.; Matyjaszewski, K.
<x xml:space="preserve">Abstract</x> Polylactide (PLA) is a class of promising biomaterials that hold great promise for various biological and biomedical applications, particularly in the field of vascular tissue engineering where it can be used as a fibrous mesh to coat the inside of vascular prostheses. However, its hydrophobic surface providing nonspecific interactions and its limited ability to further modifications are challenges that need to be overcome. Here, the development of new air‐spun PLA nanofibers modified with hydrophilic surfaces exhibiting reduction response is reported. Surface‐initiated atom transfer radical polymerization allows for grafting pendant oligo(ethylene oxide)‐containing polymethacrylate (POEOMA) from PLA air‐spun fibers labeled with disulfide linkages. The resulting PLA‐ss‐POEOMA fibers exhibit enhanced thermal stability and improved surface properties, as well as thiol‐responsive shedding of hydrophilic POEOMA by the cleavage of its disulfide linkages in response to reductive reactions, thus tuning the surface properties. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>